The Biological and Behavioural Effects of Electroconvulsive Stimulus in Rodents: Investigation and Translational Implications of a Genetic Animal Model of Depression - Kyeremanteng, Catherine (Université d'Ottawa / University of Ottawa, 2012)
Electroconvulsive therapy (ECT) is one of the oldest and most effective treatments for depression; however, its biological underpinnings are poorly understood. Brain-derived neurotrophic factor (BDNF) and the hypothalamic-pituitary-adrenal (HPA) axis are two chemical messenger systems implicated in the antidepressant action and cognitive side effects of ECT. The Wistar-Kyoto (WKY) strain is a genetic model of depression that shows biological, cognitive, behavioural, and treatment-response abnormalities, making it potentially a useful model in which to investigate the underpinnings of the action of electroconvulsive stimulus (ECS: the amimal model of ECT). In addition, the WKY presents a potentially useful model for translational research on depression. The WKY strain is particularly valuable for the measurement of serum BDNF protein, for which the association with antidepressant treatments is much less clear (mostly stemming from investigations in humans) than that between brain BDNF and antidepressant treatments in rodent studies. The three studies presented add insight into the biological and behavioural effects of ECS. The first study (chapter 2) found no evidence of increased (R)-[11C]rolipram binding (an indirect marker of cyclic-adenosine monophosphate, cAMP) in the brain, despite significant increases of brain BDNF protein expression after repeated ECS. The second study (chapter 3) demonstrated the validity of the WKY strain in the investigation of ECS. Relative to Wistar controls, WKY showed similar antidepressant and cognitive effects (despite some abnormal behavioural responses), immediate but not sustained increases in brain BDNF protein, and a novel finding of increased extra-hypothalamic CRF after 5 daily ECS. The final study (chapter 4) demonstrated baseline strain differences in serum (WKY < Wistar) but not brain BDNF and, in both strains, no change in serum BDNF despite significant changes in brain BDNF after repeated ECS treatment. Preliminary results from a human pilot study investigating similar measures in a small group of people receiving ECT for depression are also presented. The results of this body of work advance our understanding of the activation and role of brain and serum measures of BDNF and the HPA axis in ECS/ECT, and raise important issues in the translation of research from basic science to the human condition of depression.
Keywords: Depression; Rodent models; Electroconvulsive Therapy; Electroconvulsive Stimulation; Brain-Derived Neurotrophic Factor; Corticotropin Releasing Factor; Wistar Kyoto; Memory